A Newly Designed Collagen-Based Bilayered Scaffold for Skin Tissue Regeneration - Uzunalan, Gurhan; Ozturk, Merve Tuzlakoglu; Dincer, Sevil; Tuzlakoglu, Kadriye (Journal of Composites and Biodegradable Polymers, 2013)
In this study, a bilayered collagen-based membrane was prepared to mimic skin structure as a potential candidate for wound dressing application. To achieve the desired bilayered structure similar to skin, freeze-drying and electrospinning methods were used consecutively. The macroporous sublayer was prepared by freeze-drying of collagen intended for the absorption of exudates, while the upper layer was electrospun onto the freeze-dried part as an impermeable part to microorganisms. Nanofiber layer was loaded with silver nanoparticles for antibacterial activity. In order to improve biostability, double-layered materials were crosslinked by glutaraldehyde vapor. The morphology of the developed structures was assessed by SEM and the integrity of two layers was confirmed. The water uptake capacity of the scaffolds in physiological conditions was found to be around 738%. Afterwards, silver nanoparticles were sprayed to the upper part in order to obtain an antibacterial layer, and fibrinogen was immobilized to the sublayer for the stimulation of healing process. Agar zone inhibition test showed the antibacterial characteristics of the scaffolds. By providing structural and chemical similarity to natural skin tissue, the designed material can be a potential scaffold for skin tissue regeneration.